FRUIT BODY PRODUCTION AND CHARACTERIZATION OF HYBRID EDIBLE MUSHROOM STRAINS DEVELOPED BY PROTOPLAST FUSION BETWEEN PLEUROTUS FLORIDA AND LENTINUS SQUARROSULUS - P MALLICK; SR SIKDAR (International Journal of Pharma and Bio Sciences, 2015)
Polyethylene glycol (PEG)-mediated protoplast fusion between Pleurotus florida and Lentinus squarrosulus successfully developed twelve pfls somatic hybrids using double selection screening method. Hybridity was proved by the colony morphology, mycelial growth, hyphal traits, fruit body parameters and RFLP profiling of rRNA-ITS region. ANOVA is used for phenotypic data analysis of the pfls hybrids and parents. Out of twelve, only six pfls hybrid could produce basidiocarp on paddy straw substrate in sub-tropical climate and showed phenotypic resemblance to the P. florida parent. PCA analysis showed maximum positive correlation between each phenotypic variable for all strains examined in which the highest influential variables were found between cell width and yield. The amplified rRNA-ITS bands were ranged from 620 bp to 700 bp in size in all the samples tested. Restriction enzymes AluI, HinfI, HpaII and HaeIII were found to be highly polymorphic after digestion of rRNA-ITS products for all the pfls hybrids and parents. A total of 96 RFLP fragments were was produced for all in which HaeIII showed the maximum (34) and HpaII showed the minimum (16) restriction fragments in gel. The digested fragments were ranged from 160 bp to 680 bp in size.